2022
DOI: 10.1111/1365-2745.14037
|View full text |Cite
|
Sign up to set email alerts
|

Increased nutrient availability speeds up permafrost development, while goose grazing slows it down in a Canadian High Arctic wetland

Abstract: 1. It is of prime importance to understand feedbacks due to the release of carbon (C) stored in permafrost soils (permafrost-climate feedback) and direct impacts of climatic variations on permafrost dynamics therefore received considerable attention. However, indirect effects of global change, such as the variation in soil nutrient availability and grazing pressure, can alter soil and surface properties of the Arctic tundra, with the potential to modify soil heat transfers toward the permafrost and impact resi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 133 publications
(152 reference statements)
0
8
0
Order By: Relevance
“…However, snow geese can consume up to 60% of the annual production of wetland graminoids in the High Arctic (Gauthier et al., 1995; Valéry et al., 2010). Their grazing can thus alter the competitive balance between mosses and vascular plants by removing graminoid biomass, preventing litter accumulation, and changing the soil thermal profile and hydrology, which indirectly promotes high moss biomass (Deschamps et al., 2022; Gauthier et al., 2004). Our study adds to these effects of goose foraging as we found that goose presence increases alpha diversity and promotes moss coexistence.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…However, snow geese can consume up to 60% of the annual production of wetland graminoids in the High Arctic (Gauthier et al., 1995; Valéry et al., 2010). Their grazing can thus alter the competitive balance between mosses and vascular plants by removing graminoid biomass, preventing litter accumulation, and changing the soil thermal profile and hydrology, which indirectly promotes high moss biomass (Deschamps et al., 2022; Gauthier et al., 2004). Our study adds to these effects of goose foraging as we found that goose presence increases alpha diversity and promotes moss coexistence.…”
Section: Discussionmentioning
confidence: 99%
“…Snow geese probably influence species composition both directly and indirectly; for example, when they grub for rhizomes, they disturb the moss carpet by creating holes that may be colonized by various moss species (Jasmin et al., 2008). In addition, in the absence of grazing of vascular plants, litter accumulates (Deschamps et al., 2022), and competition for light probably limits the growth of moss species (an indirect effect). Thus, snow geese can act as a filter on plant community composition.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Rather, plant biomass typically has been measured as part of individual research projects, each with its own focus and protocols. For instance, researchers have investigated how plant biomass is affected by climate 23 , 24 , wildfire 25 28 , herbivores 29 , 30 , and soil properties such as texture, nutrients, and pH 31 33 . Researchers have also measured plant biomass to assess ecosystem carbon storage 34 , 35 , evaluate terrestrial ecosystem models 36 , and map spatial patterns of plant biomass from landscape to biome scales by linking field and remote sensing measurements 37 – 40 .…”
Section: Background and Summarymentioning
confidence: 99%